2018
DOI: 10.19111/bulletinofmre.500553
|View full text |Cite
|
Sign up to set email alerts
|

ACTIVE TECTONIC AND PALEOSEISMOLOGIC CHARACTERISTICS OF THE YENİCE-GÖNEN FAULT, NW TURKEY, IN LIGHT OF THE 18 MARCH 1953 YENİCE-GÖNEN EARTHQUAKE (Ms=7.2)

Abstract: The Yenice-Gönen Fault (YGF) is located in the central part of the Biga Peninsula between Gönen and Yenice and is a right-lateral strike-slip active fault with general trending N65°E. On 18 March 1953 there was an earthquake on the YGF that died 263 people (Ms=7.2) and a 70 km surface rupture developed during this earthquake. In this study measurements of slip distribution were performed on the surface rupture of the Yenice-Gönen Earthquake (YGE) and the annual slip rate on the YGF was calculated. Right-latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Mozafari et al, (2019) stated that at least three earthquakes rupture identified between 3.6 ka to 15 ka with an estimated long-term slip rate of 1.0 mm/y for Kalafat Fault, between 2.0 ka and 7.9 ka with an estimated long-term slip rate of 0.6 mm/y for Yavansu Fault. According to their results, the recurrence interval did not follow a uniform trend like other active faults in Western Anatolia (e.g., Kürçer et al, 2019). For these reasons, the possibility of triggering of these faults, which have not produced earthquake for a long time, due to the Samos earthquake should be examined.…”
Section: Discussionmentioning
confidence: 94%
“…Mozafari et al, (2019) stated that at least three earthquakes rupture identified between 3.6 ka to 15 ka with an estimated long-term slip rate of 1.0 mm/y for Kalafat Fault, between 2.0 ka and 7.9 ka with an estimated long-term slip rate of 0.6 mm/y for Yavansu Fault. According to their results, the recurrence interval did not follow a uniform trend like other active faults in Western Anatolia (e.g., Kürçer et al, 2019). For these reasons, the possibility of triggering of these faults, which have not produced earthquake for a long time, due to the Samos earthquake should be examined.…”
Section: Discussionmentioning
confidence: 94%
“…The Marmara Region has been characterized by high seismic activity with tens of devastating large earthquakes in both historical (Figure 1a) and instrumental period (Figure 1b) [1,2,3,4,5]. The trench studies have confirmed the high seismic activity [6,7,8,9,10,11]. The high seismic activity has been generated by the North Anatolian Fault Zone (NAFZ) which extends as three main fault strands, the Northern, Middle and Southern strands [12,13,14] (Figure 1a).…”
Section: Introductionmentioning
confidence: 97%
“…These strands could together accommodate as much as 25% of the total slip of the NAF (Armijo et al., 2002; Flerit et al., 2003), with slip rates between 7 and less than 1 mm/yr on the MNAF estimated with geodetical (Ergintav et al., 2014; Özbey et al., 2021; Reilinger et al., 2006) and geological data (Gasperini et al., 2011; Özalp et al., 2013; Vardar et al., 2014). While the SNAF experienced a Mw 7.2 earthquake in 1953 (Ketin & Rösli, 1953; Kürçer et al., 2008, 2019), no major earthquake ruptured the MNAF during the instrumental period, and the seismicity of the MNAF zone during the last eight decades does not include more than a couple of earthquakes larger than Mw 5. The microseismicity recently recorded has been mostly located west of Iznik Lake and around the Gulf of Gemlik, while the other segments in the east have been characterized by much fewer events and appear quiescent compared with the neighboring NAF strands (Baris et al., 2002; Gürbüz et al., 2000; Öztürk et al., 2009; Tsukuda et al., 1988).…”
Section: Introductionmentioning
confidence: 99%